Respuesta :

Step-by-step explanation:

[tex]f(x) = {x}^{2} + 3 \\ \therefore \:f(2) = {2}^{2} + 3 = 4 + 3 = 7 \\ \\ g(x) = 2x - 1 \\ \therefore \:g(2) = 2 \times 2 - 1 = 4 - 1 = 3 \\ \\ a) \:fg(2) = f(2) \times g(2) = 7 \times 3 = 21 \\ \\ b) \:gf(2) = g(2) \times f(2) = 3 \times 7= 21 \\ [/tex]

Good morning ☕️

Answer:

[tex]fg(2) = 12\\\\gf(2) = 13[/tex]

Step-by-step explanation:

f(2) = 2² + 3 = 7

g(2) = 2(2) - 1 = 3

fg(2) = f(3) = 3² + 3 = 12

gf(2) = g(7) = 2(7) - 1 = 14 - 1 = 13

_______________________

:)

ACCESS MORE